The beginning and end of all things: a biblical theology of creation and new creation - Klink, Edward W. (IVP Academic, 2023)
"Edward W. Klink III presents a holistic understanding of creation, one that is unfolded throughout all of Scripture and is at the core of the gospel itself. Along with offering rich insights about God and his purposes for the world, a biblical theology of creation guides how we engage nature, culture, and life as embodied beings"--